2020
DOI: 10.1097/j.jcrs.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating intraoperative dynamics and safety in posterior polar cataract with intraoperative OCT-guided phacoemulsification

Abstract: Purpose: To evaluate morphological characteristics and intraoperative dynamics of posterior polar cataract (PPC) using intraoperative optical coherence tomography (iOCT). Setting: Rajendra Prasad Center for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India. Design: Prospective interventional study. Methods: Forty eyes with PPC undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“… 19 Recently, Titiyal et al used iOCT to assess real-time PC integrity of posterior polar cataracts and proved that it characterized high-risk morphological features, which were consistent with the deficient morphology detected by AS-OCT in their previous report. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Recently, Titiyal et al used iOCT to assess real-time PC integrity of posterior polar cataracts and proved that it characterized high-risk morphological features, which were consistent with the deficient morphology detected by AS-OCT in their previous report. 15 …”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Titiyal et al reported the intraoperative dynamics and safety in posterior polar cataract with iOCT-guided cataract surgery in adult patients. 15 However, to our knowledge, no study has assessed the PC during surgery in pediatric patients with posterior lens opacity. In this article, we evaluated the role of iOCT in understanding the integrity of the PC in pediatric cataracts with posterior lens opacity.…”
mentioning
confidence: 99%
“…In 2016, Amir-Asgari et al assessed the effect of swirling/pinballing lens fragments in the anterior chamber and the endothelial damage that these fragments can cause, finding that smaller particles with higher velocity tend to inflict more damage than larger, slower moving particles [112]. Titiyal et al used the iOCT to investigate morphological characteristics and dynamics of white cataracts and posterior polar cataracts [113,114]. Distinct characteristics of white cataract that were observed on OCT in different degrees included; the convexity of the anterior capsule, arrangement and reflectance of cortical fibers, presence of clefts, and homogenous ground glass appearance [114].…”
Section: Cataract Surgerymentioning
confidence: 99%
“…Distinct characteristics of white cataract that were observed on OCT in different degrees included; the convexity of the anterior capsule, arrangement and reflectance of cortical fibers, presence of clefts, and homogenous ground glass appearance [114]. In posterior polar cataract they identified differences in delineating of the posterior capsule, reflectivity of the posterior polar opacity and underlying capsule, and adherence of the opacity to the posterior capsule [113]. Based on these features the authors propose new classification systems for these types of cataract, thereby aiding patient care and future research.…”
Section: Cataract Surgerymentioning
confidence: 99%
“…Titiyal et al in a prospective study evaluated the morphological characteristics of posterior polar cataracts using iOCT and were able to demonstrate 3 morphological variations that had implications on the intraoperative surgical maneuvers performed. 16 In this issue, Chen et al (page 261) for the first time demonstrate the use of iOCT during pediatric cataract surgery. They were able to morphologically characterize pediatric posterior polar cataracts and differentiate between posterior lenticonus and posterior polar cataracts.…”
mentioning
confidence: 99%